Perspektif Ibu Hamil Tentang Peran Suami dalam Pemenuhan Gizi Selama Trimester I di Wilayah Kerja Puskesmas Seginim - Liya Lugita Sari (Jurnal Asuhan Ibu dan Anak, 2019)
ABSTRACT The role of a husband is very needed to remind his wife to always consume adequate nutrition during pregnancy. Support and the role of the husbands during pregnancy are proven to increase the readiness of pregnant women to face the labor, even production of breast milk. This study aimed to determine the pregnancy women’s perspective about the role of a husband in fulfilling nutrition during first trimester pregnancy in work area of Seginim health center of South Bengkulu regency in 2019. This study used descriptive quantitative design. The population in this study was all of first trimester pregnant women who checked their pregnancy in Seginim health center from January until February 2019 with 79 respondents as the sample. The result of Univariat analysis showed that from 79 respondents, there were 61 respondents (77.2 %) with less prespective and 18 respondents (22.8 %) with sufficient perspective.